PENERAPAN PELAPORAN PAJAK MENGGUNAKAN E-FILING - Rustan Rustan; Syifa Ainun Qalbi; Muhammad Rusyidi (Universitas Muhammadiyah Makassar, 2020)
Director General of Taxes provides easy service for Taxpayers in reporting the amount of tax that must be paid because Taxpayers do not need to come directly to the Tax Office to fulfill their tax obligations in terms of SPT submission, for Electronic Technology tax officers they can facilitate database management. The application of e-filling is a step that is expected to be able to provide excellent service to the community so that it can increase the satisfaction of taxpayers as well as the application of e-filing which is expected to provide satisfaction to taxpayers. This study aims to determine the application of tax reporting using e-Filing and taxpayer satisfaction with tax reporting using e-Filing at KPP Pratama, North Makassar. This study uses a type of descriptive qualitative research, trying to find out how the application of e-Filing as a new application in SPT delivery as well as how compulsory satisfaction with the use of e-Filing in delivering annual SPT. The data used in this study are secondary and primary data.